Silver Sulfide Nanosheets: 2D Ductile Transition Metal Chalcogenides (TMCs): Novel High‐Performance Ag2S Nanosheets for Ultrafast Photonics (Advanced Optical Materials 6/2020). Issue 6 (19th March 2020) - Feng, Jiangjiang; Li, Xiaohui; Shi, Zhaojiang; Zheng, Chuang; Li, Xuwei; Leng, Deying; Wang, Yamin; Liu, Jie; Zhu, Lujun
Abstract : Two‐dimensional Ag2 S – with its large absorption coefficient, broadband optical response, extraordinary metal‐like ductility, high plastic deformation strain, unique layered structure, and very low solubility – offers a platform for achieving tremendous success in various fields of photonics. In article number 1901762, Xiaohui Li and co‐workers experimentally realize ultrashort soliton operation based on a 2D Ag2 S saturable absorber integrated into a fiber laser. The 229th harmonic soliton molecule achieves a repetition rate of 1.1 GHz in the telecommunication band.